2022
DOI: 10.1021/acsami.2c09607
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Two-Dimensional Benzodifuran-Based Polymer for Eco-Friendly Perovskite Solar Cells Featuring High Stability

Abstract: Perovskite solar cells (PSCs) have been regarded as an exceptional renewable energy conversion technology due to their rapidly increasing photovoltaic efficiency, while their practical application is highly retarded by their intrinsic instability and potential lead ion leakage. Here, a two-dimensional (2D) π-conjugated benzodifuran-based polymer, PBDFP-Bz, is adopted to modify the perovskite film. Note that PBDFP-Bz could neutralize surface defects, fine-tune interfacial energetics, and hamper moisture ingress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
(75 reference statements)
0
11
0
Order By: Relevance
“…Two-dimensional (2D) π-conjugated PBDFP-Bz with abundant functional groups can interact strongly with the perovskite film surface to neutralize surface defects. 86 FTIR measurements confirmed that the C-H, C-O, and C-F bonds in PBDFP-Bz interacted with PbI 2 to prevent lead leakage. After immersing the device with PBDFP-Bz in DI water for 7200 min, the lead concentration in the DI water was detected to be 18.9 ppm, which is much lower than that of the control device (>60 ppm).…”
Section: Other Materialsmentioning
confidence: 68%
See 1 more Smart Citation
“…Two-dimensional (2D) π-conjugated PBDFP-Bz with abundant functional groups can interact strongly with the perovskite film surface to neutralize surface defects. 86 FTIR measurements confirmed that the C-H, C-O, and C-F bonds in PBDFP-Bz interacted with PbI 2 to prevent lead leakage. After immersing the device with PBDFP-Bz in DI water for 7200 min, the lead concentration in the DI water was detected to be 18.9 ppm, which is much lower than that of the control device (>60 ppm).…”
Section: Other Materialsmentioning
confidence: 68%
“…Two‐dimensional (2D) π‐conjugated PBDFP‐Bz with abundant functional groups can interact strongly with the perovskite film surface to neutralize surface defects 86 . FTIR measurements confirmed that the C‐H, C‐O, and C‐F bonds in PBDFP‐Bz interacted with PbI 2 to prevent lead leakage.…”
Section: Pb Immobilization Technologiesmentioning
confidence: 94%
“…Despite much effort, unluckily, device operational stability has been main bottleneck for further development. For example, external encapsulation strategy as a necessary craft process not only can prevent the infiltration of moisture and oxygen, but also enable lead sequestration, thus enhancing the environmental stability of perovskites [ 21 23 ]. Nevertheless, PSCs treated under continuous light illumination still show poor operational stability, though devices were dealt with external encapsulation.…”
Section: Introductionmentioning
confidence: 99%
“…As presented in Figure 2e, the stretching vibration of CH bond in 1,4-dithiane presents positive shift from 2985/2910 to 3000/2920 cm −1 in the 1,4-dithiane/ PbI 2 complex (Figure 2e). [34] Meanwhile, the stretching vibration of PbI bond in PbI 2 shifts from 2931/2861 cm −1 toward higher wavenumber of 2973/2872 cm −1 (Figure 2e; Figure S8, Supporting Information). However, the stretching vibration of CS bond in pure 1,4-dithiane shifts from 903 cm −1 to lower wavenumber of 898 cm −1 when complexed with PbI 2 (Figure 2f).…”
Section: Resultsmentioning
confidence: 99%